(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article analyzes the experience of designing a personalized multifunctional educational space on the example of an Autonomous non–profit educational organization "Khoroshevskaya School" - a school in which a personalized education model is implemented. The key aspects of the organization of the educational process and extracurricular activities are revealed. The portrait of a pupil is considered from the point of view of the groups of skills and "over-abilities" embedded in his structure. The specifics of the formation of subject, flexible and digital skills in a personalized educational space are revealed. The characteristic of the process of organizing control and evaluation activities is given. The importance of the personal plan of teaching as the basis for the formation of awareness and responsibility for one’s own choice is actualized. The spatial-subject component of the organization of the educational environment is described.